2017
DOI: 10.1016/j.asjsur.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde jejunogastric intussusception: A case report and review of the literature

Abstract: Retrograde jejunogastric intussusception (JGI) is a rare but potentially fatal complication after previous gastrectomy or gastric bypass surgery. Because of the prevalence of bariatric surgery, the number of cases of postoperative intussusception has increased markedly. Here, we present the case of a patient with retrograde jejunogastric intussusception, having a previous history of subtotal gastrectomy and gastrojejunostomy for peptic ulcer disease. Correct preoperative diagnosis was made by plain abdominal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 15 publications
1
44
0
10
Order By: Relevance
“…Ultrasonography shows a tubular mass with peristalsis and computed tomography (CT) scan will show intussusception (9). Upper gastrointestinal endoscopy helps in the diagnosis and can be therapeutic in reducing the retrograde jejuno-gastric intussusception (9). In our case, diagnosis was confirmed on barium contrast study and Computerised tomography abdomen.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Ultrasonography shows a tubular mass with peristalsis and computed tomography (CT) scan will show intussusception (9). Upper gastrointestinal endoscopy helps in the diagnosis and can be therapeutic in reducing the retrograde jejuno-gastric intussusception (9). In our case, diagnosis was confirmed on barium contrast study and Computerised tomography abdomen.…”
Section: Discussionsupporting
confidence: 56%
“…A water-soluble upper gastrointestinal contrast study reveals a "coiled -spring" appearance of the intussusception. Ultrasonography shows a tubular mass with peristalsis and computed tomography (CT) scan will show intussusception (9). Upper gastrointestinal endoscopy helps in the diagnosis and can be therapeutic in reducing the retrograde jejuno-gastric intussusception (9).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic reduction is associated with recurrence. 24 Ultrasound findings reveal a mass with echogenic center surrounded by concentric echogenic rings with a peripheral rim of hypoechogenicity. On transverse images, this rim has been described as doughnut sign and longitudinal images as pseudo kidney sign.…”
Section: -49-11mentioning
confidence: 99%
“…6,15,25,26 Laparoscopic examination with reduction of of the intussusception via a minilaparotomy wound. 24 To prevent recurrence few authors suggested fixation of jejunum to the adjacent tissue, mesocolon, colon, stomach or faliciform ligament. 14,24,27 The role of fixation has been debated as the chance of recurrence is rare.…”
Section: -49-11mentioning
confidence: 99%
See 1 more Smart Citation